Upaya Meningkatkan Kemampuan Santri dalam Menyusun Menu Gizi Seimbang di Pondok Pesantren Hidayatullah Putri Kota Kendari - Euis Nurlaela; Rasmaniar Rasmaniar (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The system of providing Islamic boarding school education requires its students to stay permanently in the boarding school during learning activities and skip meals in the boarding school, this condition requires the commitment of the Islamic boarding school to provide the best possible food so that the nutritional needs of the students are still fulfilled. One of the efforts to meet nutritional needs is through menu planning according to nutritional needs and balanced nutrition guidelines, so that it is necessary to empower students who are involved in food processing. The aim is to provide knowledge and practice of compiling a balanced nutritional menu to students. Located at the Hidayatullah Putri Islamic Boarding School, the target is 30 female students aged 10-15 years. The method used is lecture, discussion and practice of preparing menus. The evaluation was carried out 3 times, namely pre test, post test 1 and post test 2. The results of the activity obtained that the level of knowledge of students before receiving counseling was included in the sufficient category, only 3.33% after being given counseling (post test 1) increased to 66.67% in the sufficient category. and 10% in good category, in post test 2 the category is sufficient 40% and good category 30%, while the ability of students to prepare menus before being given practice is 100% in the poor category, after being given practice in compiling menus (post test 1), 40% is in sufficient category and 10 % in good category, in post test 2 60% in sufficient category and 13.33% in good category. ABSTRAK Sistem penyelenggaraan pendidikan pondok pesantren mengharuskan para santrinya untuk tinggal menetap di pondok selama kegiatan belajar dan melewati waktu makan di dalam pondok, kondisi ini menuntut komitmen pondok pesantren untuk menyediakan makanan sebaik mungkin agar kebutuhan zat gizi santri tetap tercukupi. Salah satu upaya untuk memenuhi kebutuhan zat gizi melalui perencanaan menu sesuai kebutuhan gizi dan pedoman gizi seimbang, sehingga diperlukan pemberdayaan santri yang ikut terlibat dalam pengolahan makanan. Tujuan memberikan pengetahuan dan praktik menyusun menu gizi seimbang  kepada santri. Bertempat di Pondok Pesantren Hidayatullah Putri, sasaran remaja putri usia 10 – 15 tahun sebanyak 30 santri. Metode yang digunakan adalah ceramah, diskusi serta praktik penyusun menu. Evaluasi dilakukan 3 kali yaitu pre test, post test 1 dan post test 2. Hasil kegiatan diperoleh tingkat Pengetahuan santri sebelum memperoleh penyuluhan termasuk kategori cukup hanya sebesar 3,33% setelah diberikan penyuluhan (post test 1) meningkat menjadi 66,67% kategori cukup dan 10% kategori baik, pada post test 2 kategori cukup 40% dan kategori baik 30%, sedangkan kemampuan santri menyusun menu sebelum diberikan praktik 100% kategori kurang, setelah diberikan praktik menyusun menu (post test 1) sebesar 40% kategori cukup dan 10% kategori baik, pada post test 2 sebesar 60% kategori cukup dan 13,33% kategori baik.